Failure causes and effect analysis of water supply systems - C-tin, Ionescu Gheorghe; Smaranda, Ionescu Daniela; Daroczi, Carol (Acta Agraria Debreceniensis, 2010)
The present paper intends to overview the problems of the failure causes and effect analysis of water supply systems. The author’s efforts were channeled to systemizing, classifying and adapting the content to the hydraulics engineering field.